Evaluation of Silver Nanoparticles Based on Fresh Cocoa Pods (Theobroma Cacao) Extracts as New Potential Electrode Material - Alex Vincent Somba; Evangéline Njanja; Gullit Deffo; Cyrille Ghislain Fotsop; Kevin Yemele Tajeu; Armel Florian Tchangou Njiemou; François Eya’ane Meva; Theophile Kamgaing (Journal of Chemistry)
This work focuses on the synthesis of silver nanoparticles using fresh cocoa pods from the “Theobroma cacao” extract plant through the reduction of silver ions (Ag+) into Ag (0) by a green chemistry process, subsequently used as an electrode material. Reaction factors such as pH, incubation time, and silver ion concentration were optimized during the formation of nanoparticles. The synthesized nanoparticles were characterized by ultraviolet spectrophotometry (UV-Vis), Fourier transform infrared spectroscopy (FT-IR), powder X-ray diffraction (PXRD), scanning electron microscopy (SEM), and energy dispersive X-ray spectrometry (EDX) analysis. Once drop coating was applied on the glassy carbon electrode (GCE), the resulting film was characterized using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The results show that silver nanoparticles have been well synthesized and can find applications as electrode materials for simultaneous determination of ascorbic acid and uric acid in aqueous solution.